Societal extinction of species. (May 2022) - Jarić, Ivan; Roll, Uri; Bonaiuto, Marino; Brook, Barry W.; Courchamp, Franck; Firth, Josh A.; Gaston, Kevin J.; Heger, Tina; Jeschke, Jonathan M.; Ladle, Richard J.; Meinard, Yves; Roberts, David L.; et al.
Abstract : The ongoing global biodiversity crisis not only involves biological extinctions, but also the loss of experience and the gradual fading of cultural knowledge and collective memory of species. We refer to this phenomenon as 'societal extinction of species' and apply it to both extinct and extant taxa. We describe the underlying concepts as well as the mechanisms and factors that affect this process, discuss its main implications, and identify mitigation measures. Societal extinction is cognitively intractable, but it is tied to biological extinction and thus has important consequences for conservation policy and management. It affects societal perceptions of the severity of anthropogenic impacts and of true extinction rates, erodes societal support for conservation efforts, and causes the loss of cultural heritage. Highlights: Just as population declines may lead to biological extinction, the decline of collective attention and memory may lead to the societal extinction of species. Direct and vicarious experiences with species affect their societal salience and likelihood of societal extinction. Societal extinctions affect perceptions of the environment, lead to a shifting baseline syndrome, hinder establishment of more ambitious conservation/restoration targets, and diminish support for conservation efforts. Several mitigation actions, relying predominantly on conservation education and marketing, are needed to reduce or reverse the societal extinction of species.